Thoracic Manifestations of Genitourinary Neoplasms and Treatment-related Complications. Issue 3 (May 2019) - Stowell, Justin T.; Betancourt-Cuellar, Sonia L.; Carter, Brett W.; Wu, Carol C.; Walker, Christopher M.
Abstract : Genitourinary (GU) malignancies are a diverse group of common and uncommon neoplasms that may be associated with significant mortality. Metastases from GU neoplasms are frequently encountered in the chest, and virtually all thoracic structures can be involved. Although the most common imaging manifestations include hematogenous dissemination manifesting with peripheral predominant bilateral pulmonary nodules and lymphatic metastases manifesting with mediastinal and hilar lymphadenopathy, some GU malignancies exhibit unique features. We review the general patterns, pathways, and thoracic imaging features of renal, adrenal, urothelial, prostatic, and testicular metastatic neoplasms, as well as provide a discussion of treatment-related complications that might manifest in the chest. Detailed reporting of these patterns will allow the imager to assist the referring clinicians and surgeons in accurate determination of the stage, prognosis, and treatment options available for the patient. Awareness of specific treatment-related complications further allows the imager to enhance patient safety through accurate and timely reporting of potentially life-threatening consequences of therapies.